Rebel writers : the accidental feminists : Shelagh Delaney, Edna O'Brien, Lynne Reid-Banks, Charlotte Bingham, Nell Dunn, Virginia Ironside, Margaret Forster /: the accidental feminists : Shelagh Delaney, Edna O'Brien, Lynne Reid-Banks, Charlotte Bingham, Nell Dunn, Virginia Ironside, Margaret Forster. (2019) - Brayfield, Celia
No abstract available